Optimalisasi Pengawasan Foreign Object Debrish (FOD) Oleh Petugas AMC Di Bandar Udara Internasional Haji Ahmad Sanusi Hanandjoeddin - M. Rifki Zaelani P; Awan Awan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Foreign Object Debris is any object, any object that is alive or not lying in an improper place around the airport environment that could allow an accident to airport personnel and damage an aircraft. This study aims to determine the Optimization of Foreign Object Debrish (FOD) Supervision by AMC Officers at H.A.S Hanandjoeddin International Airport and obstacles in Optimizing Foreign Object Debrish (FOD) Supervision by AMC Officers at H.A.S Hanandjoeddin International Airport and how to overcome them. This study used a qualitative method with data sources in the form of primary data and secondary data. Data collection techniques include observation, interviews, and documentation. Data validity techniques use source triangulation and triangulation techniques. Data analysis techniques used include data reduction, data presentation, and conclusions. The result of this study is that the supervision of the AMC unit on Foreign Object Debrish (FOD) by AMC officers at H.A.S Hanandjoeddin International Airport is carried out, which is in accordance with SOPs and supervision carried out in coordination with the unit (Safety Risk, Quality Control TJQ) and routinely conducts FOD walks every 1 month, Supervision of AMC officers related to Foreign Object Debrish (FOD) standard by conducting socialization to Ground Handling to conduct daily FOD checks before parking aircraft and handling. FOD supervision is carried out by the AMC unit in the morning before operating hours, flight lag times, and the last flight. The supervision is carried out by giving directions to GH (ground handling) to maintain each other's cleanliness. Obstacles in Optimizing Foreign Object Debrish (FOD) Supervision by AMC Officers at H.A.S Hanandjoeddin International Airport include: lack of facilities, and lack of passenger awareness. How to overcome obstacles in the application of optimizing Foreign Object Debrish (FOD) supervision by AMC officers at H.A.S Hanandjoeddin International Airport, is to hold facilities such as CCTV or FOD detection cameras and runway cleaning car tools and socialize passengers about the dangers of FOD to increase passenger awareness so as not to throw garbage when passing through the apron area, Distribute brochures and attach appeals and sanctions for violators of the rules so that passengers can be aware of the dangers of throwing garbage around the airport area, especially the airside area and provide trash cans in the airside area to prevent passengers from littering.